SUN-182 Rare Case of Adrenocortical Carcinoma with Tumor Extension into the Inferior Venacava, Right Atrium and Right Ventricle - Siddiqi, Asmat Qayoom (J Endocr Soc, 2020)
Introduction: Adrenocortical carcinoma is a rare and highly aggressive malignancy with an incidence rate of 1-2 per million population per year. It is an aggressive tumor with early metastasis to lungs, liver, bone and lymph nodes. Venous tumor thrombosis to inferior venacava (IVC), atrium or ventricle is rare and is considered as a tumor extension instead of metastatic disease, but with a poor prognostic outcome. Clinical Case: We present a rare case of adrenocortical carcinoma with tumor extension into the IVC, right atrium and right ventricle. A 62-year-old female with history of breast cancer on anastrozole presented to the clinic for a routine screening colonoscopy. Patient was noted to have uncontrolled hypertension before the procedure, so was sent to the ER. Upon further interviewing she complained of increasing abdominal distension, hirsutism, and bilateral lower extremity swelling over the past six months. CT abdomen revealed a large 10 x11 x13 cm heterogeneously enhancing mass arising above the right kidney, with extensive tumor extension into the IVC, right atrium and right ventricle. MRI too characterized a large mass in the right adrenal gland with tumor thrombus extension into the IVC, right atrium, and right ventricle. Hormonal studies demonstrated elevated cortisol, dehydroepiandrosterone-sulfate and testosterone levels. A 1 mg dexamethasone suppression test inadequately suppressed cortisol levels, consistent with Cushing’s syndrome due to endogenous over secretion of cortisol. Free plasma and urine metanephrine levels were normal. Plasma renin and aldosterone concentration were within normal limits. With the cooperation of a multidisciplinary team, patient underwent right adrenalectomy with removal of tumor thrombus from right atrium and right ventricle under cardiopulmonary bypass. Surgical pathology confirmed adrenocortical carcinoma. She was started on mitotane as adjuvant therapy. Patient was also noted to have a lung nodule with biopsy showing oncocytic neoplasm favoring metastasis from adrenal cortex. She did receive chemotherapy for the lung metastasis with decrease in the size of the nodule. Conclusion: Adrenal cortical carcinoma is a rare disease and the venous tumor thrombus to IVC, atrium and ventricle is even rarer and has a poor prognostic outcome. Complete tumor resection is the only curative approach with adjuvant therapies aiming to decrease the risk of recurrence only. Due to the aggressive nature of the tumor and quick development of metastasis, early diagnosis gives the best chance of resection and hence the greatest chances of survival.